GENERAL CULTURAL COMPETENCES AND EDUCATIONAL TECHNOLOGIES - Leonid S. Grebnev (Высшее образование в России)
The article discusses an experience of building such general cultural competences as communication abilities, team%working, effective coordination with colleges, self% organization and self%education in the frames of auditorium practices and self%reliant work of students of psychological department of National Research University Higher School of Economics.